Let's face it : - Douglas, Kirk (John Wiley & Sons, 2007)
In Let's Face It, Douglas reflects on how his Jewish faith has become more and more important to him over the years. He offers strong opinions on everything from anti-Semitism to corporate greed, from racism to Hurricane Katrina, and from the war in Iraq to the situation in Israel. He writes about the importance in his life of the need to improve education for all children and about how we need to care more about the world and less about ourselves.